135 ACCURACY OF ACHALSIA QUALITY OF LIFE AND ECKARDT SCORES FOR ASSESSMENT OF CLINICAL IMPROVEMENT POST TREATMENT FOR ACHALASIA. (14th September 2020) - Slone, S; Richter, J; Kumar, A; Velanovich, V; Jacobs, J
Abstract: : Achalasia Quality of Life (ASQ) and Eckardt scores are two patient-reported instruments used to assess symptom severity in achalasia patients. ASQ is validated and reliable. Although Eckardt is commonly used, it has not been assessed for validity or reliability. Our aims were to evaluate 1) the accuracy of both instruments for assessing improvement post-treatment (predictive validity) with pneumatic dilatation versus surgical myotomy and 2) convergent validity of both tools. Methods: Patients with achalasia treated between 2011–2018 were eligible. Both instruments were administered by telephone. Treatment failure was determined by review of medical records by two clinicians. The predictive ability of ASQ and Eckardt instruments in identifying treatment successes and failures was determined using receiver operating characteristics analysis and summarized as Area Under the Curve (AUC). Results: 106 patients met inclusion criteria with 44 PD, 52 Heller Myotomy, and 10 per-oral endoscopic myotomy. A review of medical records and esophageal testing defined 13 failures (13%). AUC for Eckardt was 0.96 [95% CI 0.87–0.99] and ASQ 0.97 [95% CI 0.92–0.99]. The Eckardt cutoff 4, and ASQ, cutoff 15, were 94% and 87% accurate in identifying treatment successes versus failures. The correlation coefficient between the two tools was 0.84. Conclusion: 1) ASQ and Eckardt scores are valid and reliable tools to assess symptom severity in achalasia patients; 2) Both instruments accurately classify treatment successes versus failures. 3) The choice of tool should be informed by the physicians' and patients' values and preferences and repeat physiologic testing may be reserved for treatment failures with either instrument and patients classified as treatment successes may be spared routine physiologic testing in the long term.